2002
DOI: 10.1039/b201477g
|View full text |Cite
|
Sign up to set email alerts
|

The aqueous environment in AOT and Triton X-100 (w/o) microemulsions probed by fluorescence

Abstract: The confined aqueous medium of Triton X-100/cyclohexane-hexanol/water microemulsions was studied and compared with that of AOT/isooctane/water. The microenvironment generated was assessed by following the photophysical behaviour of the cationic dye, acridine orange (AO). This dye presents an acid-base equilibrium in free bulk water (pKa approximately equal to 10.2) which is clearly affected in Triton X-100 microemulsions where the neutral species is stabilised at low omega0. The addition of water contributes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 40 publications
4
33
0
Order By: Relevance
“…The state of solubilized water in the aqueous core of reverse microemulsions has been widely studied 26. 29, 3638 In the AOT‐based reverse microemulsions, only a few initial water molecules are needed to solvate the interface, and the remaining water molecules are available to form water pools; but, in TX‐100 aqueous microemulsions, there is a higher demand for hydration water 38. It has been suggested that the inner core water molecules have a strong tendency to form a hydrogen‐bonded bridged structure between two adjacent OE groups 39.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The state of solubilized water in the aqueous core of reverse microemulsions has been widely studied 26. 29, 3638 In the AOT‐based reverse microemulsions, only a few initial water molecules are needed to solvate the interface, and the remaining water molecules are available to form water pools; but, in TX‐100 aqueous microemulsions, there is a higher demand for hydration water 38. It has been suggested that the inner core water molecules have a strong tendency to form a hydrogen‐bonded bridged structure between two adjacent OE groups 39.…”
Section: Resultsmentioning
confidence: 99%
“…[38] It has been suggested that the inner core water molecules have a strong tendency to form a hydrogenbonded bridged structure between two adjacent OE groups. [39] An oblate form is observed in the TX-100 aqueous microemulsion, due to the longer size of the hydrophilic groups of TX-100.…”
Section: Possible Structure Of the Il/o Microemulsionmentioning
confidence: 99%
“…Previously, Andrade et al have observed a Lewis base character of TX-100 in the interaction with another dye, acridine orange. 48 In the present case also, it is possible that TX-100 acts as a Lewis base toward 7H4MC, and thus, a part of the dye molecules form a kind of contact ion pair (7H4MC δ-/TX-100 δ+ , I) at the interfacial region, which absorbs in the longer-wavelength region (∼370 nm). Such an ion pair formation with a corresponding absorption band in the longer-wavelength region has also been reported for 7H4MC dye with the bases like triethyl amine in some nonhydroxylic solvents.…”
Section: Absorption and Fluorescence Spectral Features And Time-resolmentioning
confidence: 97%
“…To estimate the maximum number of heparin chains within a CPC-GAG cluster, the hydrodynamic volume of the cluster was assumed to be of (19,54). spherical shape (V h ¼ 4=3pR 3 h ) and was divided by the volume of a single heparin chain saturated with the defined number of ligands as measured by ITC.…”
Section: Dynamic Light Scatteringmentioning
confidence: 99%